Preșcolaritatea fericită – premisa unei adolescențe echilibrate - Brânză, Mihaela (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
Early childhood represents an essential period in the life of a person. Parents have plenty of responsabilities to carry out. A Christian family builds a happy life asking unceasingly the help of God. The attention required by a baby from the first day should be offered without restraint. Every baby needs happy adults that react positively to its emotional expressions. When the two adults do their best to take care of the baby, avoiding unpleasant and traumatic experiences such as quarrelling nearby, the baby feels comfortable and confident to discover the world around it. The baby plays a lot and adults should not interrupt its attempt to find out more about the surroundings. This activity develops its perseverance and will. Thus adults should offer the best care during the first seven years of life. Communication with the child means a constant effort to answer their child’s questions, playing with it and respecting its capacity to make decisions and carry out things by itself. The reciprocal respect must be built during the early childhood. The religious education is important in this critical development phase because it teaches the child to use the Christian knowledge about God as a landmark for the rest of the life.